Efektivitas Teknik Role Playing dalam Layanan Bimbingan Kelompok untuk Pengembangan Sosial dan Emosional Peserta Didik - Denisa Septiani; Juwita Madira; Dea Kartika Utami; Berlian Cahyani; Ratna Sari Dewi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
The aim of this study is to determine the extent to which role-playing methods can be optimally applied in group counseling sessions as an approach to develop students' social and emotional skills. The method used is a literature review of articles published between 2015 and 2025 that discuss the application of role-playing techniques in the context of guidance and counseling. The findings indicate that this technique is effective in enhancing interpersonal and intrapersonal communication, self-confidence, self-esteem, solidarity, assertive behavior, and self-efficacy. Additionally, role-playing can reduce negative behaviors such as bullying, verbal aggression, social anxiety, and gadget addiction. The simulation of real-life situations in this technique provides space for reflection and active learning for students. Therefore, role-playing is recommended as an interactive and applicable method that is relevant to group counseling services to support students' holistic development.